“Why are you hiding here?”: Counter-Narrating Antisemitic Master-Narratives in Bernard Malamud’s The Fixer - Sklar, Howard (Narrative Works)

(untitled) (Centre for Digital Scholarship, University of New Brunswick, 2024)
When Mendel Beilis, a Jew, was accused of having murdered a Christian child in Kyiv in 1911, the allegations drew on centuries-old “blood libel” legends, dating back to the Middle Ages, in which Jews purportedly sacrificed Christian children for ritual purposes. While Beilis eventually was acquitted of the charges, the master-narratives that drove them have proved resistant to counter-narration. Bernard Malamud’s 1966 novel The Fixer, by fictionally attempting to retell Beilis’s story through the character of Yakov Bok, provides a “critical reinterpretation […] of dominant narrative models” (Meretoja 2021)—a powerful counter-narrative, not only to the specific tale of Beilis, but also to the longer-standing claims that continue to buttress antisemitism.